2016
DOI: 10.1001/jama.2016.1869
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hypertensive Disorders of Pregnancy and Later Risk of Cardiomyopathy

Abstract: IMPORTANCE Women with hypertensive disorders of pregnancy, preeclampsia in particular, have an increased risk of cardiomyopathy during the peripartum period. Whether hypertensive disorders of pregnancy are also associated with cardiomyopathy later in life is unknown.OBJECTIVE To determine whether hypertensive disorders of pregnancy are associated with cardiomyopathy beyond the peripartum period. DESIGN, SETTING, AND PARTICIPANTSNationwide register-based cohort study using Cox regression to compare rates of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 35 publications
3
58
0
1
Order By: Relevance
“…Our results were generally consistent with previous studies in showing that women with HDP had adverse levels of cardiovascular risk factors at various time points from before first pregnancy and until menopause,6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 with correspondingly increased risks of hypertension, obesity, and diabetes mellitus 13, 14, 15, 39, 40, 41, 42. Our study adds to the limited evidence beyond age 50 years, confirming that except for lipids, for which trajectories converge by age 60 years, other differences in cardiovascular risk factors persist until age 60 years.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were generally consistent with previous studies in showing that women with HDP had adverse levels of cardiovascular risk factors at various time points from before first pregnancy and until menopause,6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 with correspondingly increased risks of hypertension, obesity, and diabetes mellitus 13, 14, 15, 39, 40, 41, 42. Our study adds to the limited evidence beyond age 50 years, confirming that except for lipids, for which trajectories converge by age 60 years, other differences in cardiovascular risk factors persist until age 60 years.…”
Section: Discussionsupporting
confidence: 92%
“…30,33 Recent work has indicated that women who experience cardiovascular complications or hypertensive disorders in pregnancy are at sharply increased risks of cardiomyopathy, acute myocardial infarction, stroke, or new-onset heart failure beginning within just a few years of giving birth. 54–56 Altered vascular function also may increase the risk of adverse pregnancy outcomes and placental insufficiency. Increased maternal plasma levels of endothelial markers during pregnancy, including VCAM1 and ICAM1, have been implicated in the development of pre-eclampsia, fetal endothelial function and increased risk of preterm delivery and lower birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence reveals that maternal morbid events may be associated with the long‐term health of women. In particular, an increased risk of morbidity and mortality from cardiovascular and cerebrovascular complications in women who had placenta‐related complications during pregnancy has been concordantly reported . These results are of major importance for two reasons: first, in terms of understanding of the pathophysiology of pregnancy complications possibly related to placenta ischemia – gestational hypertension, pre‐eclampsia, abruption and intrauterine growth restriction – and second, in terms of prenatal and postpartum care for women who experience these complications during pregnancy.…”
mentioning
confidence: 88%